Chimeric Peptides/Proteins Encoded by circRNA: An Update on Mechanisms and Functions in Human Cancers - Khan, Faiz Ali; Nsengimana, Bernard; Khan, Nazeer Hussain; Song, Zhenhua; Ngowi, Ebenezeri Erasto; Wang, Yunyun; Zhang, Weijuan; Ji, Shaoping (Frontiers in Oncology, 2022)
The discovery of circular RNAs and exploration of their biological functions are increasingly attracting attention in cell bio-sciences. Owing to their unique characteristics of being highly conserved, having a relatively longer half-life, and involvement in RNA maturation, transportation, epigenetic regulation, and transcription of genes, it has been accepted that circRNAs play critical roles in the variety of cellular processes. One of the critical importance of these circRNAs is the presence of small open reading frames that enable them to encode peptides/proteins. In particular, these encoded peptides/proteins mediate essential cellular activities such as proliferation, invasion, epithelial–mesenchymal transition, and apoptosis and develop an association with the development and progression of cancers by modulating diverse signaling pathways. In addition, these peptides have potential roles as biomarkers for the prognosis of cancer and are being used as drug targets against tumorigenesis. In the present review, we thoroughly discussed the biogenesis of circRNAs and their functional mechanisms along with a special emphasis on the reported chimeric peptides/proteins encoded by circRNAs. Additionally, this review provides a perspective regarding the opportunities and challenges to the potential use of circRNAs in cancer diagnosis and therapeutic targets in clinics.